Draco’s Constitution in the Athenaion Politeia 4: Is It an Interpolation or an Author’s Later Addition? - Verlinsky, Alexander (Hyperboreus, 2017)
The paper reconsiders Draco’s constitution (DC) in ch. 4 of Aristotle’ Athenaion Politeia, which is widely held to be an interpolation in the text (or, minimally, an author’s later addition). The present paper is an attempt to prove that neither argument – neither that from the structure of the text of the ﬁrst chapters of the AP nor the argument from the omission of number with DC in the list of constitutional changes (ch. 41) and the discrepancy in the total number of changes (eleven instead of twelve) does not prove that DC was later inserted into the text in any way. At the same time the attempts to explain the awkwardness in ch. 41 through the supposition that DC is not depicted in ch. 4 as a constitution in its own right and thus proving it to be an integral part of the text are misleading. The confusion in ch. 41 is related to the double status of the change under Theseus which preceded the one under Draco: it is called the second change (i.e. second institutional change), but the ﬁrst constitutional one. The ﬁrst change absolutely, that which took place under Ion, was thus not constitutional, and this change, and not that which took place under Draco, was not counted.